The Implementation of Multilingual Habituation in Enhancing Students’ Self-Confidence - Rahmanita, Rahmanita; Fitriani, Saparia; Fauzani, Fatmi; Febriany, Fina; Yafni, Lazi; Anggella, Isra’ (STIT Ahlussunnah Bukittinggi, 2026)
This study aims to examine the implementation of multilingual habituation practices and their contribution to enhancing students’ self-confidence. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis related to the use of Indonesian, Arabic, and English in both classroom activities and daily interactions within the school environment. The findings reveal that multilingual habituation is implemented in a structured and sustainable manner through regular language practice, guided conversations, and support from teachers as well as student language ambassadors. These practices positively influence students’ development across cognitive, affective, and conative domains, while also fostering greater confidence in communication. Increased self-confidence is reflected in students’ willingness to use foreign languages in everyday interactions without excessive fear or anxiety. This study highlights that multilingual habituation not only contributes to language proficiency but also strengthens students’ psychological development, particularly their self-confidence.